Sustained censorship in IR (2026-02) (Iran) - Voidly (2026)
CRITICAL severity censorship detected in Iran. Confidence: 80%. Data sourced from OONI.
Censorship Incident ID: IR-2026-0390
Keywords: censorship; IR; censorship; critical